Ordinary Muon Capture for Double Beta Decay and Anti-Neutrino Nuclear Responses - Hashim, Izyan Hazwani; Ejiri, Hiroyasu (Frontiers in Astronomy and Space Sciences, 2021)
This is a brief review on ordinary muon capture (OMC) experiments at Research Center for Nuclear Physics (RCNP) Osaka University relevant for the study of double beta decays (DBDs) and astro anti-neutrinos (neutrino) nuclear responses. OMC usually leaves the nucleus in highly excited unbound state. OMC is a charge exchange reaction via the charged weak boson as given by (μ,vμ) reactions with μ and vμ being the muon and muon neutrino. Subjects discussed include 1) unique features of OMC for studying DBDs and astro anti-neutrino (neutrino) nuclear responses, 2) experiments of OMCs on 100Mo and natMo to study neutrino nuclear responses for DBDs and astro anti-neutrinos, 3) impact of the OMC results on neutrino nuclear responses for DBDs and astro anti-neutrinos. Remarks and perspectives on OMC experiments for neutrino nuclear responses are briefly described.